A novel IL‐23p19/Ebi3 (IL‐39) cytokine mediates inflammation in Lupus‐like mice. Issue 6 (13th April 2016) - Wang, Xiaoqian; Wei, Yinxiang; Xiao, He; Liu, Xiaoling; Zhang, Yu; Han, Gencheng; Chen, Guojiang; Hou, Chunmei; Ma, Ning; Shen, Beifen; Li, Yan; Egwuagu, Charles E.; et al.
Abstract : Promiscuous chain‐pairing of IL‐12 subunit proteins predicts six possible IL‐12 family members. We have discovered IL‐39 (IL‐23p19/Ebi3) as newest IL‐12 member that signals through its cognate receptor (IL‐23R/gp130) and STAT1/STAT3 pathways. IL‐39 is secreted by activated B cells of Lupus‐like mice and might therefore contribute to immune‐pathogenic mechanisms of Lupus . Abstract : Interleukin‐12 family cytokines have emerged as critical regulators of immunity with some members (IL‐12, IL‐23) associated with disease pathogenesis while others (IL‐27, IL‐35) mitigate autoimmune diseases. Each IL‐12 family member is comprised of an α and a β chain, and chain‐sharing is a key feature. Although four bona fide members have thus far been described, promiscuous chain‐pairing between alpha (IL‐23p19, IL‐27p28, IL‐12/IL‐35p35) and beta (IL‐12/IL‐23p40, IL‐27/IL‐35Ebi3) subunits, predicts six possible heterodimeric IL‐12 family cytokines. Here, we describe a new IL‐12 member composed of IL‐23p19 and Ebi3 heterodimer (IL‐39) that is secreted by LPS‐stimulated B cells and GL7 + activated B cells of lupus‐like mice. We further show that IL‐39 mediates inflammatory responses through activation of STAT1/STAT3 in lupus‐like mice. Taken together, our results show that IL‐39 might contribute to immunopathogenic mechanisms of systemic lupus erythematosus, and could be used as a possible target for its treatment.